2014
DOI: 10.1590/s0100-83582014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Weed control in corn and weed sample size for growth evaluations

Abstract: -The objectives of this study were to evaluate baby corn yield, green corn yield, and grain yield in corn cultivar BM 3061, with weed control achieved via a combination of hoeing and intercropping with gliricidia, and determine how sample size influences weed growth evaluation accuracy. A randomized block design with ten replicates was used. The cultivar was submitted to the following treatments: A = hoeings at 20 and 40 days after corn sowing (DACS), B = hoeing at 20 DACS + gliricidia sowing after hoeing, C =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Various methods include soil covering (Rajashekarappa et al, 2013), incorporation of plant residues (Matloob et al, 2010;Khaliq et al, 2011), spraying with vegetable extracts (Mubeen et al, 2012;Uddin et al, 2013), and intercropping (Tavella et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods include soil covering (Rajashekarappa et al, 2013), incorporation of plant residues (Matloob et al, 2010;Khaliq et al, 2011), spraying with vegetable extracts (Mubeen et al, 2012;Uddin et al, 2013), and intercropping (Tavella et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have demonstrated that various perennial species may control weeds when grown with corn (Tavella et al, 2014). In these studies, corn has been intercropped with tree species individually, i.e., corn + gliricidia (Gliricidia sepium) or corn + sabiá (Mimosa caesalpiniifolia).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with this, the reduction of synthetic herbicides in agriculture production has been considered in many countries because humans perceive the negative aspects of chemical overuse in weed control such as the problems of food safety, environmental pollution, undesirable effects on living organisms, and the appearance of herbicide-resistance (Al Samarai et al, 2018). Therefore, non-chemical methods to control weeds have been studied in corn, including management of cover plants and increased corn planting densities (Tavella et al, 2014) Living cover crops suppress weeds during their growing phases and act as living mulch by competing for resource availability (light, nutrients, and water). They create a canopy for a greater number of crop plants in a unit area (Kumar et al, 2017) and through physical, biotic, and allelopathybased inhibition of weed germination interactions (Radicetti, 2012;Lemessa & Wakjira, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Embora na literatura exista inúmeros trabalhos para determinar tamanhos de parcela, de amostra e número de repetições alguns deles no café (Coffea arabica L.) (CIPRIANO et al, 2012;GUARÇONI et al, 2020), no milho (Zea mays, L.)( CATAPATTI et al, 2008;TAVELLA et al, 2014;TOEBE et al, 2014;VARGAS ROJAS;NAVARRO FLORES, 2017;TOEBE, 2020), e na soja (Glycine max L. Merril) (CARGNELUTTI FILHO et al, 2009;STORCK et al, 2009;GONÇALVES, 2011;BELMONTE et al, 2020), observa-se que não é possível determinar o mesmo tamanho de parcela/amostra para todos os caracteres agronômicos ou padronizar para todas as culturas.…”
Section: Introductionunclassified